2020
DOI: 10.4028/www.scientific.net/kem.840.284
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Antimicrobial Screening of Actinomycetes from the Soil of Enggano Island, Indonesia

Abstract: Actinomycetes are filamentous Gram-positive bacteria that potential sources of antimicrobial substances. The aim of this study was to isolate actinomycetes from different soil types in Enggano Island and screened their antimicrobial activity. The phenol method with 802 medium and humic acid vitamin (HVA) medium was used to isolate the actinomycetes. Furthermore, molecular identifications were performed based on 16s rRNA gene sequence. Antimicrobial activity screening was performed against Bacillus subtilis BTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Our preliminary research supports further investigation of the isolate SHP 9-3, which showed prominent broadspectrum antimicrobial activity (Pahira et al 2020). Based on the 16S rRNA analysis, the isolate was identified as S. koyangensis SHP 9-3.…”
Section: Characteristics Of Streptomyces Koyangensis Strain Shp 9-3supporting
confidence: 72%
See 3 more Smart Citations
“…Our preliminary research supports further investigation of the isolate SHP 9-3, which showed prominent broadspectrum antimicrobial activity (Pahira et al 2020). Based on the 16S rRNA analysis, the isolate was identified as S. koyangensis SHP 9-3.…”
Section: Characteristics Of Streptomyces Koyangensis Strain Shp 9-3supporting
confidence: 72%
“…The S. koyangensis strain SHP 9-3 was isolated from the soil of Enggano Island, Bengkulu, Indonesia (Pahira et al 2020). Cultivation of S. koyangensis SHP 9-3 was carried out on the International Streptomyces Project-2 (ISP-2) media (consisting of 4 g yeast extract, 10 g malt extract, 4 g glucose in 1 L water, pH 7.0) for 7-14 days at 37°C (Ratnakomala et al 2016).…”
Section: Preparation Of Streptomyces Koyangensis Strain Shp 9-3mentioning
confidence: 99%
See 2 more Smart Citations